Synthesis and reactivity of TADDOL-based chiral Fe(ii) PNP pincer complexes-solution equilibria between κ2P, N- and κ3P, N, P-bound PNP pincer ligands1. Issue 29 (7th August 2015) - Holzhacker, Christian; Stöger, Berthold; Carvalho, Maria Deus; Ferreira, Liliana P.; Pittenauer, Ernst; Allmaier, Günter; Veiros, Luis F.; Realista, Sara; Gil, Adrià; Calhorda, Maria José; Müller, Danny; Kirchner, Karl
<x xml:space="preserve">Abstract</x> Fe(ii) complexes bearing chiral PNP pincer ligands based on R, R-TADDOL are described.